Climate change and tropical marine ecosystems: A review with an emphasis on coral reefs (UNED Research Journal, 2019)
Climate change is usually associated with warming and weather extremes that impact the human environment and terrestrial systems, but it also has profound effects on the ocean, which is probably the most unique, life-supporting feature of planet Earth. The most direct consequence of rising CO2 concentration in the atmosphere is “ocean acidification,” a term that refers to the lowering of seawater pH, but encompasses a suite of chemical changes that affect marine organisms from shell formation, to reproduction, physiology, and behavior. The oceans are also warming in pace with the atmosphere, and in fact store the vast majority of the additional heat generated by rising CO2 and other greenhouse gases in the atmosphere. This warming is causing the more mobile marine species to redistribute poleward and deeper, and is causing high mortality in more sessile species such as those that build and habituate coral reefs. But warming is also leading to a decrease in dissolved oxygen in the oceans. For tropical marine ecosystems, the combination of ocean acidification, warming, and deoxygenation will continue to impact marine ecosystems in the future. The extent of these impacts depends on which energy pathway society follows, and our abilities to reduce other stressors and assist the rate at which species can adapt and migrate to more suitable environments.
Keywords: oceans; climate change; ocean acidification; ocean warming; ocean deoxygenation